From universal literature classics to social sciences: mapping three intranslation projects in Mexico - Tania Paola Hernandez-Hernandez (Cadernos de Tradução)
The concept “intranslation” was coined in 1992 to refer to the importation of foreign books into a national language via translation. Since then, the concept has travelled, and its meaning has expanded to describe other aspects of the international production, circulation and reception of texts, such as the symbolic and material spaces, capitals and practices involved in these processes. With the purpose of continuing to explore its explanatory power, in this article I argue intranslation has been the dominant process in Mexico’s translation policies of the 20th century. I examine three intranslation projects supported and/or implemented by the Mexican government. The article is divided into two main sections. The first section outlines the concepts of translation policy, intranslation and extranslation. The second section begins with an overview of the evolution of the Mexican publishing field. This is followed by a description of three translation projects supported by the Mexican government and by the analysis of the evolution of the roles and values attributed to translation.